Elizabeth Vesey and the Art of Educating Oneself, Between London and Lucan - Maria Stefanelli (Studi Irlandesi, 2013)
A 1926 publication describes the Library of Mrs. Elizabeth Vesey (1715- 1791), a Bluestocking and the wife, by second marriage, of Agmondisham Vesey, a member of the Irish Parliament. The essay examines the books that refer to the cultural background and critical abilities of an Irish literary lady who transmitted but a small record of her literary competence to posterity. The excursus points to her historical, philosophical, and theological formation as the daughter of the Bishop of Ossory, besides her acquaintance with foreign literatures (most prominently the Italian one) and her ideological involvement with the question of the American colonies that she only briefly hints at in a letter to her friend Mrs. Montague in order not to trespass the borders of the public sphere. Vesey’s portrait would be mostly imperfect if this collection was ignored.